Changes in Body/Tissue Composition of Rats in Relation to Dietary Protein Levels during Rehabilitation. - Viswanathan, K.R.; Swamy, M. Siddaling; Prasad, N. Narayan (Defence Science Journal, 2013)
Effect of rehabilitation with marginally sub-optimal and adequate levels of dietary protein following a 50 per cent diet restriction for 10 days was studied in adult rats, The data revealed hyperphagia, supernormal weight gain and greater food efficiency in rehabilitated animals which progressively tapered off on days 9 and lO, irrespective of the dietary protein level. However, the values remained slightly higher than their respective controls. The food efficiency ratio and nitrogen balance which followed the above pattern, on the other hand, returned to control levels in the group that was refed 20 percent protein diet. The weights of liver and muscles of 20 per cent protein diet group were higher than those of 10 per cent protein diet group, while the fat pad weight showed a reverse trend. This was observed only in the case of control and rehabilitated animals. The liver lipid and protein concentrations were less in rehabilitated rats as compared to their ad libitum fed counterparts. The carcasses of control as well as rehabilitated animals on 10 per cent protein diet had less moisture and more fat content than those on 20 per cent protein diet. The carcass in 20 per cent protein diet group had a higher protein content. A linear correlation was observed between body weight and body fat, while a reciprocal relationship existed between the body fat and body water regardless of whether the rats were rehabilitated or restricted fed.